Lolly Willowes, o, El amante cazador - Warner, Sylvia Townsend, 1893-1978; Montolió, Célia; Warner, Sylvia Townsend, 1893-1978. ([Madrid] : Siruela, 2016)
The story of a middle-aged spinster who moves to a country village to escape her controlling relatives and takes up the practice of witchcraft.
Online resource; title from ePub title page (Digitalia, viewed April 27, 2017)
Keywords: Single women -- England -- Social conditions -- Fiction; Witches -- England -- Fiction; Paranormal fiction; Electronic books